Prophylactic treatment of vestibular migraine - Salmito,Márcio Cavalcante (2017)
Abstract Introduction: Vestibular migraine (VM) is now accepted as a common cause of episodic vertigo. Treatment of VM involves two situations: the vestibular symptom attacks and the period between attacks. For the latter, some prophylaxis methods can be used. The current recommendation is to use the same prophylactic drugs used for migraines, including β-blockers, antidepressants and anticonvulsants. The recent diagnostic definition of vestibular migraine makes the number of studies on its treatment scarce. Objective: To evaluate the efficacy of prophylactic treatment used in patients from a VM outpatient clinic. Methods: Review of medical records from patients with VM according to the criteria of the Bárány Society/International Headache Society of 2012 criteria. The drugs used in the treatment and treatment response obtained through the visual analog scale (VAS) for dizziness and headache were assessed. The pre and post-treatment VAS scores were compared (the improvement was evaluated together and individually, per drug used). Associations with clinical subgroups of patients were also assessed. Results: Of the 88 assessed records, 47 were eligible. We included patients that met the diagnostic criteria for VM and excluded those whose medical records were illegible and those of patients with other disorders causing dizziness and/or headache that did not meet the 2012 criteria for VM. 80.9% of the patients showed improvement with prophylaxis (p < 0.001). Amitriptyline, Flunarizine, Propranolol and Topiramate improved vestibular symptoms (p < 0.001) and headache (p < 0.015). The four drugs were effective in a statistically significant manner. There was a positive statistical association between the time of vestibular symptoms and clinical improvement. There was no additional benefit in hypertensive patients who used antihypertensive drugs as prophylaxis or depressed patients who used antidepressants in relation to other prophylactic drugs. Drug association did not show statistically significant results in relation to the use of a single drug. Conclusions: Prophylactic medications used to treat VM improve the symptoms of this disease, but there is no statistically significant difference between the responses of prophylactic drugs. The time of vestibular symptom seems to increase the benefit with prophylactic treatment.